The Use of Eye-Movement Desensitization Reprocessing (EMDR) Therapy in Treating Post-traumatic Stress Disorder—A Systematic Narrative Review - Wilson, Gemma; Farrell, Derek; Barron, Ian; Hutchins, Jonathan; Whybrow, Dean; Kiernan, Matthew D. (Frontiers in Psychology, 2018)
Aim: There is an extensive body of research examining the efficacy of Eye-Movement Desensitisation Reprocessing (EMDR) therapy in treatment of Post-Traumatic Stress Disorder (PTSD). This systematic narrative review aimed to systematically, and narratively, review robust evidence from Randomised-Controlled Trials examining the efficacy of EMDR therapy. Method: Eight databases were searched to identify studies relevant to the study aim. Two separate systematic searches of published, peer-reviewed evidence were carried out, considering relevant studies published prior to April 2017. After exclusion of all irrelevant, or non-robust, studies, a total of two meta-analyses and four Randomised-Controlled Trials were included for review. Results: Data from meta-analyses and Randomised-Controlled Trials included in this review evidence the efficacy of EMDR therapy as a treatment for PTSD. Specifically, EMDR therapy improved PTSD diagnosis, reduced PTSD symptoms, and reduced other trauma-related symptoms. EMDR therapy was evidenced as being more effective than other trauma treatments, and was shown to be an effective therapy when delivered with different cultures. However, limitations to the current evidence exist, and much current evidence relies on small sample sizes and provides limited follow-up data. Conclusions: This systematic narrative review contributes to the current evidence base, and provides recommendations for practice and future research. This review highlights the need for additional research to further examine the use of EMDR therapy for PTSD in a range of clinical populations and cultural contexts.